Must see places of the world. 6, Scenic cruises of the world [videorecording (DVD)] - Gullason, David; Singer, Lynette; Townsley, Graham; Gardner, Andrew (Reader's digest classic collection., 2009)
Shows a number of cruising locations in North and Central America, Europe, and several of the Pacific islands, including Nova Scotia, Cape Breton, the Caribbean, Guatemala, the Panama Canal, Big Sur, Alaska, Norway, Scotland, the Rhine, France, Lisbon, Gibraltar, Greece, the Nile, Chile, Easter Island, Tahiti, New Zealand, Austrailia, Fiji, and Hawaii.